Evaluation of the Serum Levels of Interleukin-6, Interleukin-10, and C-Reactive Protein in Iraqi Women with Breast Cancer - Ibraheem Muhesin, Ashjan; Abbas Hadi, Abdul-Hadi (Al-Kufa University Journal for Biology, 2023)
Breast cancer is the most prevalent form of cancer in women and is the leading cause of global cancer-related mortality. The study aimed to assess the changes in some serum biomarkers linked to immunity responses in Iraqi breast cancer patients and understand their multifaceted role in the disease's progression. The current investigation comprised a cohort of 55 women diagnosed with breast cancer and a control group of 45 healthy participants. The levels of interleukin-6 (IL-6), interleukin-10 (IL-10), and C-reactive protein (CRP) were estimated in the serum of breast cancer patients. The results showed that patients with breast cancer had a significant increase (p<0.05) in IL-6, IL-10, and CRP serum concentrations as compared to healthy women. These findings give support to the evidence suggesting that these markers may play an essential role in the progression of breast cancer.